Distribution extension of a rare species, Eumops auripendulus in the province of Santa Fe, Argentina - Montani, María Eugenia; Saigo, Germán; Villa, Irene M. (Therya Notes, 2023)
The presence of Eumops auripendulus (Chiroptera, Molossidae) in the province of Santa Fe, Argentina, is recorded. Until now, this species in Santa Fe was known from a single record from Esperanza in 1978. A new specimen was obtained in the town of Florencia, located about 400 km NE of Esperanza, near the border with the province of Chaco. This new record corresponds to an animal that was found dead and sent to the Laboratorio Central de la Dirección General de Bioquímica y Farmacia of Santa Fe in 2019 as part of the rabies virus surveillance protocol. The species was identified based on its morphometric variables and its general aspect. On the other hand, its geographical location was plotted on a map together with the rest of the records of this species in the country; the ecoregional context was also considered. This new record confirms the current presence of the species in the province and helps to clarify its geographic distribution range as well as its ecological preferences, considering that both localities are situated in different ecoregions: Espinal (Esperanza) and Humid Chaco (Florencia). It is important to mention that E. auripendulus has been poorly studied in Argentina, being known only from 10 records in 3 provinces: Chaco, Misiones, and Santa Fe.